Performance and Analysis of Pediatric Index of Mortality 3 Score in a Pediatric ICU in Latifa Hospital, Dubai, UAE - Dinesh Malhotra; Nadine Nour; Mahmoud El Halik; Marwan Zidan (Dubai Medical Journal)
Introduction: The pediatric index of mortality (PIM) 3 is one of several severity scoring systems used for predicting the outcome of patients admitted to pediatric intensive care units (PICUs) based on data collected within the first hour of admission. It avoids potential bias from the effects of treatment after admission and offers practical utility in assigning children to clinical trials soon after PICU admission. PIM 3 is an updated version of PIM 2 for predicting mortality in the PICU. It provides an international standard based on a large contemporary dataset for the comparison of risk-adjusted mortality among children admitted to intensive care. Objective: The aim was to evaluate the performance of the PIM 3 score in predicting mortality in a tertiary care PICU. Materials and Methods: This was a cohort observational study conducted at a tertiary care PICU from January 2016 to October 2018. All patients between 1 month and 15 years of age who were admitted in the PICU in Latifa Hospital were included. PIM 3 scoring was done for all the patients. All data were extracted from the computerized ICU registry database. Scores were calculated using the PIM 3 calculator application. Data were entered into Microsoft Excel 2013 and analyzed using SPSS v24.0. We analyzed the association between PIM 3 score and mortality. The performance of PIM 3 score was assessed by calibration and discrimination. Calibration evaluated PIM 3 at different risks of mortality and was assessed by standardized mortality ratio (SMR) and Pearson’s χ2 goodness-of-fit test. SMR was calculated to a mean probability of death and the ratio of observed-to-expected death rates. Discrimination evaluated how well PIM distinguished between patients who survived and died and was assessed using the area under the curve (AUC) with a 95% confidence interval (CI) from the receiver-operating characteristics plot. Results: A total of 583 patients were included in the study, 46 of whom (7.9%) died. The overall SMR was 0.53. SMR was 0.33 and 0.72 in the p < 14.3% and p > 14.3% group, respectively. The expected mortality rate based on PIM 3 score was 9.2 and 37.5% in the p < 14.3% and p > 14.3% group, respectively. Conclusion: The PIM 3 was used to predict mortality in PICU patients in Latifa Hospital, Dubai. The overall accumulated expected mortality was 87.081 (5%) compared to the observed mortality of 46 (7.9%) and SMR of 0.53. PIM 3 had acceptable discrimination ability with an AUC of 0.78 (95% CI 0.69–0.87).